Hypoalbuminemia is a Predictive Factor for Fistula Formation in Recurrent Cervical Cancer. (October 2018) - Palavalli Parsons, Lavanya H.; Roane, Brandon; Manders, Dustin B.; Richardson, Debra L.; Kehoe, Siobhan M.; Carlson, Matthew; Miller, David S.; Lea, Jayanthi S.
Abstract : Objective: Antivascular endothelial growth factor monoclonal antibodies inhibit tumor angiogenesis, consequently impeding the recruitment of new vasculature to existing and new tumor lesions. We sought to evaluate toxicities in women with recurrent cervical cancer after receiving bevacizumab combination chemotherapy. Methods: A review was conducted of women with recurrent and metastatic cervical cancer who were treated with salvage chemotherapy with or without bevacizumab between 2005 and 2015. Clinicopathologic data and reasons for treatment discontinuation were recorded. Patients that were excluded had other histology than squamous or adenocarcinoma, received 1 cycle of salvage chemotherapy, single agent bevacizumab, currently on treatment, or noncompliant. Statistical analysis was performed using the Fishers Exact Test, logistic regression, and Kaplan-Meier Survival Analysis. Results: A total of 74 patients were included in analysis. Twenty-six patients were treated with bevacizumab (BEV) and chemotherapy and 48 patients with chemotherapy alone (chemotherapy). The progression free survival was significant with median 12 months versus 7 months for the BEV cohort ( P <0.01) and the overall survival was a median 74 months versus 23 months for the BEV cohort ( P =0.06). Cessation of treatment secondary to severe toxicities was seen in 46% (n=12) of BEV cohort versus 15% (n=7) of chemotherapy cohort ( P <0.01). Twenty-seven percent (n=7) of patients in the BEV cohort stopped secondary because of fistula formations. Lower albumin levels and use of bevacizumab were identified as an independent predictor factors for fistula formation ( P =0.004 and 0.024, respectively). Conclusions: Hypoalbuminemia and bevacizumab treatments are significant predictive factors of fistula formation in patients treated for recurrent cervical cancer.